2018
DOI: 10.1002/jmv.25251
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of noroviruses in children in South Greece, 2013‐2015

Abstract: Noroviruses constitute the leading cause of acute, nonbacterial gastroenteritis that affects both children and adults in healthcare and community settings. The current study attempted to provide insight on the molecular epidemiology of noroviruses in children in South Greece. Genotypic characterization of 69 norovirus strains detected in stool samples from children with gastroenteritis during a period of 30 months (January 2013 to June 2015) was performed on the basis of ORF2 (VP1 capsid) gene sequences. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
6
8
0
Order By: Relevance
“…We also observed that norovirus infection was found extensively in children <2 years old, with a significantly higher prevalence compared to that among children ≥2 years old (P = 0.01). Although norovirus infection occurred in all age groups, the children <2 years old appeared to be more vulnerable, which is consistent with other reports (Wu et al, 2020;Louya et al, 2019;Lu et al, 2019;Siafakas et al, 2018). The low prevalence of norovirus infection among older children could be due to acquired immunity through previous exposures (Gupta et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…We also observed that norovirus infection was found extensively in children <2 years old, with a significantly higher prevalence compared to that among children ≥2 years old (P = 0.01). Although norovirus infection occurred in all age groups, the children <2 years old appeared to be more vulnerable, which is consistent with other reports (Wu et al, 2020;Louya et al, 2019;Lu et al, 2019;Siafakas et al, 2018). The low prevalence of norovirus infection among older children could be due to acquired immunity through previous exposures (Gupta et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with previous studies that concluded that noroviruses mainly peaked in cold seasons [20, 22, 2628], our study demonstrated that most NoV infections were detected in autumn and winter. However, in some other areas, NoV-associated diarrhoea had a summer peak or no apparent seasonal peak, which may be connected with an increase in contaminated water and food or other unknown reasons [21, 29].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies that concluded that noroviruses mainly peaked in cold seasons [20,22,[26][27][28], our study demonstrated that most NoV infections were detected in autumn and winter. However, in some other areas, NoVassociated diarrhoea had a summer peak or no apparent seasonal peak, which may be connected with an increase in contaminated water and food or other unknown reasons [21,29].…”
Section: Discussionmentioning
confidence: 99%